Bonuses and commissions policy and its effect on revenues: دراسة تطبيقية مقارنة على شركات خدمات السيارات - بالمملكة العربية السعودية ) - Dr/Sabir Tagelsir Mohamed Abdelrahman A lkanzi (White Nile Journal for Studies and Research, 2015)
Most companies adopt commissions and bonuses policies to their sales staff in order to achieve the objective of increasing returns and revenues. but problems arise due to unstable commission and bonus policy. Most companies tend to change the policy. particularly when the amounts for commissions and bonuses increase. Such a change in policy could negatively affect returns and revenues. This research attempts to study the relationship between a stable bonuses &commission policy and sales plans. The study hypothesis are. -Stability of bonuses and commissions policy has a positive impact on revenues. - Unstudied management techniques and policies regarding bonuses and commissions policy negatively affect revenues. The research concluded with the following results and recommendations. Results -Stable bonusand commission policy for the first three years resulted in increased revenues in these years. -A change in bonus and commission policy in the last two years resulted in reduced revenues and significantly reduced profits. Recommendations: -Careful study of decisions that affects the achievement of the company's objective. T Avoidance of taking decisions that negatively affects company's future during the financial year. Taking goal congruence into consideration when establishing bonus and commission policy.